Short-lived pollutants in the Arctic: their climate impact and possible mitigation strategies - Quinn, P. K.; Bates, T. S.; Baum, E.; Doubleday, N.; Fiore, A. M.; Flanner, M.; Fridlind, A.; Garrett, T. J.; Koch, D.; Menon, S.; Shindell, D.; Stohl, A.; et al. (Atmospheric Chemistry and Physics, 2008)
Several short-lived pollutants known to impact Arctic climate may be contributing to the accelerated rates of warming observed in this region relative to the global annually averaged temperature increase. Here, we present a summary of the short-lived pollutants that impact Arctic climate including methane, tropospheric ozone, and tropospheric aerosols. For each pollutant, we provide a description of the major sources and the mechanism of forcing. We also provide the first seasonally averaged forcing and corresponding temperature response estimates focused specifically on the Arctic. The calculations indicate that the forcings due to black carbon, methane, and tropospheric ozone lead to a positive surface temperature response indicating the need to reduce emissions of these species within and outside the Arctic. Additional aerosol species may also lead to surface warming if the aerosol is coincident with thin, low lying clouds. We suggest strategies for reducing the warming based on current knowledge and discuss directions for future research to address the large remaining uncertainties.